Digital concierge on the move (Part 1) : personal travel assistant for tourists - Lai, Lysia Huimin (2010)
As technology improves rapidly these days, more mobile phones are being equipped with advance capabilities which functions with PC-like functionalities and termed as Smart phones. With the high influx of Smart phones in the mobile phone market, more people come into possession of such Smart phones, which makes them suitable for developing a digital personal travel assistant for tourists or even locals.